OXIDATIVE STRESS IS ASSOCIATED WITH LIFETIME CARDIOVASCULAR RISK STRATIFICATION IN YOUNG TO MIDDLE AGE INDIVIDUALS. (June 2018) - Rodríguez-Sánchez, E.; Navarro-García, J.A.; Aceves-Ripoll, J.; Baldan-Martin, M.; Álvarez-Llamas, G.; Calvo, E.; Cabrera, M.; Barderas, M.G.; Ruilope, L.M.; Ruiz-Hurtado, G.
Abstract : Objective: Most cardiovascular (CV) risk estimators have a 10-years perspective, assuming that young individuals are at low CV risk. The estimator QRISK®-Lifetime calculates the risk of suffering a CV disease across the lifespan. Many CV risk factors (RFs) are related to oxidative stress. Here we assess the global oxidative stress (RiskOxy-SCORE) in a young-middle age population and its relationship with QRISK®-Lifetime. Design and method: Young-middle age individuals (30–50 years old) were stratified in 1) without RFs, 2) with RFs (metabolic syndrome, hypertension, diabetes, eGFR < 80 mL/min/1.73m2) and 3) with CV event (myocardial infarction, stroke). Lifetime CV risk was calculated with QRISK®-Lifetime (https://qrisk.org/lifetime/ ). Systemic oxidative damage was determined by carbonyl groups, oxidized LDL, 8-hydroxy-2′-deoxyguanosine and xanthine oxidase (XOD) activity. Antioxidant defence was determined by total antioxidant capacity (TAC), catalase activity and superoxide dismutase (SOD) activity. Indexes of oxidative damage and antioxidant defence were calculated and combined to estimate the global level of oxidative stress (RiskOxy-SCORE). Results: Individuals with RFs double the QRISK®-Lifetime of those without RFs (41.6 ± 10.3% vs 22.5 ± 5.6%; P < 0.001). Oxidative damage markers, TAC and catalase activity are increased in individuals with RFs (P < 0.05). XOD and SOD activities remain unchanged. RiskOxy-SCORE is higher in individuals with RFs (P < 0.05). ROC analysis indicates that the RiskOxy-SCORE discriminates between individuals with and without RFs [AUC = 0.68 (0.52–0.84), P = 0.04]. The oxidative damage index has a positive correlation with QRISK®-Lifetime (r = 0.54; P < 0.001) and performs better in the ROC analysis [AUC = 0.86 (0.75–0.96), P < 0.001]. Interestingly, individuals with a CV event have lower levels of oxidative damage (P < 0.001) and antioxidant defence (P < 0.01) indexes than those with RFs. Conclusions: Young-middle age individuals with RFs have more systemic oxidative stress than those without RFs or with a CV event, which correlates with their lifetime CV risk. The normal oxidative status observed in individuals with a CV event is likely due to the implementation of a healthy lifestyle and more aggressive therapies to prevent other CV event. Awareness of the CV risk in individuals with RFs may encourage them to introduce changes in their lifestyle, leading to a reduction in the levels of oxidative stress and an improvement in their lifetime CV risk.